Impacts of 21st‐century climate change on montane habitat in the Madrean Sky Island Archipelago. Issue 10 (8th July 2019) - Yanahan, Alan D.; Moore, Wendy
Abstract: Aim: The Madrean Sky Island Archipelago is a North American biodiversity hotspot composed of 60 isolated mountains that span the Cordilleran Gap between the Rocky Mountains and the Sierra Madre Occidental. Characterized by discrete patches of high‐elevation montane habitat, these "sky islands" serve as stepping stones across a "sea" of desert scrub/grassland. Over this coming century, the region is expected to shift towards a warmer and drier climate. We used species distribution modelling to predict how the spatial distribution of montane habitat will be affected by climate change. Location: Madrean Sky Island Archipelago, south‐west United States and north‐west Mexico (latitude, 29–34°N; longitude, 107–112°W). Methods: To approximate the current distribution of montane habitat, we built species distribution models for five high‐elevation species ( Ceanothus fendleri, Pinus strobiformis, Quercus gambelii, Sciurus aberti, and Synuchus dubius ). The resulting models were projected under multiple climate change scenarios—four greenhouse gas concentration trajectories (RCP 2.6, 4.5, 6.0, and 8.5) for each of three climate models (CCSM4, MPI‐ESM‐LR, and NorESM1‐M)—to generate predicted distributions for the years 2050 and 2070. We performed chi‐squared tests to detect any future changes to total montane habitat area, and Conover–Iman tests to evaluate isolation among the discrete montane habitat patches. Results: While the climate models differ with respect to their predictions as to how severe the effects of future climate change will be, they all agree that by as early as year 2050, there will be significant montane habitat loss and increased montane habitat patch isolation across the Madrean Archipelago region under a worst‐case climate change scenario (RCP 8.5). Main conclusions: Our results suggest that under 21st‐century climate change, the Madrean Sky Islands will become increasingly isolated due to montane habitat loss. This may affect their ability to serve as stepping stones and have negative implications for the region's biodiversity.